LOW DENSITY, LOW COMPRESSION SET, LONG RECOVERY TIME POLYURETHANE FOAM - PAPA ANTONIO; CASAGRANDE GIANLUCA; LA TERRA FEDERICO (2021)
Flexible polyurethane foams are characterized in having slow recovery times, low foam densities and very low compression sets. The foams are useful in human comfort applications such as pillows and mattresses. 柔性聚氨酯泡沫的特征在于具有缓慢的恢复时间、低泡沫密度和非常低的压缩永久变形。所述泡沫适用于人体舒适应用，如枕头和床垫。